Hubungan Penguasaan Diksi dengan Kemampuan Menulis Puisi pada Siswa Kelas X Semester Genap SMAN 13 Bandar Lampung - Permanasari, Dian; Alfiawati, Riska; Rohana, Rohana; Wibowo, Siswo Edi (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This study aims to determine whether or not there is a relationship between mastery of diction and the ability to write poetry. To achieve this goal, the author uses a quantitative descriptive method, namely by analyzing the research data statistically. Analysis of the data used the product moment correlation formula. The results obtained from data analysis using statistics, it is known that rhit = 0.483, with n = 22 in the 95% confidence level. It was obtained that rtab = 0.423 and after the analysis it turned out that rhit was greater than rtab ie 0.483> 0.423. This means that the hypothesis is proven/accepted, there is a relationship between mastery of diction and the ability to write poetry in even semester X students of SMAN 13 Bandar Lampung in the 2021/2022 academic year. The direction of the relationship between Diction mastery and the ability to write poetry in class X SMA Negeri 13 Bandar Lampung Lessons 2021/2022 is positive. The close relationship between Diction mastery and the ability to write poetry in class X SMA Negeri 13 Bandar Lampung Lessons 2021/2022 is high.